Extracts from microalgae for use in cancer treatment - Omar, Abdul Rahman; Md. Yusoff, Fatimah; Mohamed Din, Mohamed Shariff; Mohamed Alitheen, Noorjahan Banu; Loh, Su Peng; Goh, Su Hua; Nigjeh, Siamak Ebrahimi; Kuppan, Perumal; Matias-Peralta, Hazel Monica (2011)
The present invention relates to crude extracts derived from the microalgae Chaetoceros calcitrans prepared by the use of ethanol or ethyl acetate, which are effective in the treatment, prevention and/or delay of progression of a proliferative disease. Preferably the extracts of the present invention are for use in the treatment, prevention and/or delay of progression of cancer, such as breast cancer. The invention furthermore describes medicaments and pharmaceutical compositions comprising the inventive extracts of Chaetoceros calcitrans. Also method for preparing extracts of Chaetoceros calcitrans are provided, which include the use of solvents, such as ethanol and ethyl acetate.